THE EFFECT OF INFLUENCER CREDIBILITY, LIVE STREAMING INTERACTIVITY, AND TRUST ON GENERATION Z'S IMPULSE BUYING BEHAVIOR FOR FASHION PRODUCTS ON TIKTOK SHOP - Raffy Majid Santoso; Miftahul Jannah; Hildiana Ariftianti (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the influence of influencer credibility, live streaming interactivity, and consumer trust on impulse buying decisions for fashion products on the TikTok Shop platform. The research adopts a quantitative approach with an explanatory research design. Data were collected through an online questionnaire distributed to 50 Generation Z respondents who have purchased fashion products via TikTok Shop’s live streaming feature, using a purposive sampling technique. Data analysis was conducted using Multiple Linear Regression with the assistance of IBM SPSS Statistics software. This study is expected to demonstrate that influencer credibility, live streaming interactivity, and consumer trust, both partially and simultaneously, have a positive and significant effect on impulse buying decisions. Practically, the findings are expected to provide strategic implications for live commerce practitioners in optimizing their sales strategies, where building credibility, delivering engaging real-time interactions, and maintaining consumer trust are key drivers of impulsive purchasing behavior among Generation Z.